Gum Arabic as an Admixture in Modified Concrete Mixed with Calcined Kaolin - Garcia Frichnes M. Mouanda; Silverster O. Abuodha; Joseph N. Thuo (Salehan Institute of Higher Education, 2022)
The use of calcined kaolin (CK) as a cementitious material in construction has attracted the interest of various researchers due to its environmental, mechanical, and physical qualities, all of which contribute to the lowering of cement usage. Studies have reported numerous problems associated with its use in concrete, apart from the ecological benefit that CK can provide. For instance, there is an issue of increased water demand due to smaller particle size, which generates much more heat in concrete, which has a detrimental effect on the mechanical and physical properties of concrete. This paper presents the analysis of an investigation aimed at using gum Arabic (GA) as a biopolymer admixture and calcined kaolin as a partial replacement of cement to improve the mechanical properties and durability of concrete. GA proportions ranged from 0 to 1% by weight of cement. Calcined kaolin (CK) was used to replace 5, 10, 15, 20, 25, and 30% of the cement content, respectively. Compressive strength, splitting tensile strength, density, strength loss, and weight loss tests were all performed to validate the structural performance of the modified concrete. The compressive tests, performed after 28 days from the time the mixture was made, demonstrated that the maximum percentage of CK that could replace cement without affecting the mechanical properties of concrete was 20%. Beyond 20%, concrete does not exhibit good compressive strength properties. The results also revealed decreased compressive strength and splitting tensile strength tests as the percentage of CK increased. After 56 days, compressive strength at 5% CK and 10% CK increased slightly by 0.743% and 1.162 %, respectively, compared to the control sample. The inclusion of 0.8%GA increased the compressive strength by 8.94% compared to the control sample (0%CK + 0%GA + 100%OPC) after 56 days. The results of durability tests showed that 0.6% GA had a higher compressive strength than other percentages containing GA. Doi: 10.28991/CEJ-2022-08-05-010 Full Text: PDF